2007
DOI: 10.1177/0193945907310241
|View full text |Cite
|
Sign up to set email alerts
|

Midwest Nursing Research Society Sage Best Paper Award: The Association of Diabetes and Older Age With the Absence of Chest Pain During Acute Coronary Syndromes

Abstract: Cardiac autonomic neuropathy associated with diabetes can cause silent myocardial ischemia and may influence the way that patients perceive symptoms of acute coronary syndromes (ACS). The purpose of this study was to examine symptoms of ACS in patients with and without diabetes while controlling for length of time with diabetes. A convenience sample of 256 patients from two large medical centers in the Midwest participated. Patients with diabetes comprised 33.2% of the sample and reported significantly less ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 28 publications
5
22
2
3
Order By: Relevance
“…Previous reports indicated that female gender, advanced age, and history of diabetes may more commonly result in an atypical AMI presentation while male gender or STEMI are associated with a typical presentation (Canto et al, 2007;Coventry et al, 2011;DeVon et al, 2008;MacInnes, 2005;Morgan, 2005). Nevertheless, this was not completely reflected in our study nor in some previous investigations (Milner et al, 2002;Thuresson et al, 2005).…”
Section: Discussioncontrasting
confidence: 91%
“…Previous reports indicated that female gender, advanced age, and history of diabetes may more commonly result in an atypical AMI presentation while male gender or STEMI are associated with a typical presentation (Canto et al, 2007;Coventry et al, 2011;DeVon et al, 2008;MacInnes, 2005;Morgan, 2005). Nevertheless, this was not completely reflected in our study nor in some previous investigations (Milner et al, 2002;Thuresson et al, 2005).…”
Section: Discussioncontrasting
confidence: 91%
“…Lack of sex‐stratified analysis has been a continuing problem in understanding the influence of sex on ACS symptoms . Earlier findings have demonstrated that older patients and patients with diabetes report less chest pain during ACS . Because women are, on average, 10 years older than men when they develop ACS, shoulder and arm pain (particularly in women) may serve as additional prompts that aid emergency medical services and triage personnel in identifying patients with ACS—particularly in the absence of chest symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients' acquired sense of control over symptoms contributed to long delay. Conversely, longer pre-hospital delay for those with diabetes is possibly explained by the fact that diabetics may suffer from neuropathies affecting their pain receptors which result in an ill-defined or silent symptom profile [55].…”
Section: Discussionmentioning
confidence: 99%